Escherichia coli adhesion portion FimH polarizes M2 macrophages to M1 macrophages in tumor microenvironment via toll-like receptor 4 - Zhang, Wei; Xu, Li; Zhang, Xiaoyan; Xu, Jianqing; Jin, Jun-O (Frontiers in Immunology, 2023)
Macrophages are key effector cells of innate immunity and play a critical role in the immune balance of disease pathogenesis, especially in the tumor microenvironment. In previous studies, we showed that FimH, an Escherichia coli adhesion portion, promoted dendritic cell activation. However, the effect of FimH in macrophage polarization has yet to be fully examined. In this study, FimH was found to promote M1 macrophage activation. In addition, FimH polarized M2 macrophages, which were induced by interleukin (IL)-4 and IL-13 into M1 macrophages were dependent on toll-like receptor 4 and myeloid differentiation factor 2. Moreover, FimH reprogramed the tumor-associated macrophage (TAM) into M1 macrophages in B16 melanoma tumor-bearing mice and promoted an inflammatory reaction in the tumor microenvironment. Furthermore, FimH promoted M1 macrophage activation, as well as the reversion of M2 macrophages into M1 macrophages in humans. Finally, FimH treatment was found to enhance the anti-cancer immunity of anti-PD-L1 antibody by the induction of M1 polarization from TAM. These results highlight the potential new role of FimH in polarizing macrophages to the M1 subtype via TLR4 signaling pathway, which may contribute to the antitumor effect.